Penggunaan E-modul Interaktif berbantuan Geogebra dalam pembelajaran Matematika : Analisis Bibliometrik - Vera Juliani Putri; Hasanuddin, Hasanuddin (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
The use of GeoGebra-assisted interactive e-modules in mathematics learning has great potential to improve students' concept understanding through dynamic and interactive visualization. This study aims to provide a bibliometric review of 20 publications over the period 2018-2024, with two main focuses: (a) reviewing the growth trajectory of studies on the use of GeoGebra in interactive e-modules; and (b) identifying the themes and topics that appear most frequently in related publications. The study was conducted using bibliometric methods on 20 selected publications during 2018-2024. Data was obtained from Google Scholar using the Publish or Perish application and analyzed using VOSviewer. The results show an increasing trend of publications since 2021. Themes such as mathematical representation and interactive learning dominate, while topics such as media validity and integration in learning models are still rarely discussed. These findings provide an important basis for the development of technology-based learning media as well as a direction for future research to be more focused and innovative. This study supports the development of technology-based digital learning media.